84 Impact of the introduction of an integrated multi-professional pathway for atrial fibrillation on long-term outcomes. (4th June 2021) - Aslam, Saadia; Vickers, Clare; Veevers, Wendy; Farrar, Layla; Hartley, Elizabeth; Viswanathan, Karthik
Abstract : Background: An integrated structured approach to atrial fibrillation (AF) management is recommended by ESC. 1 However, limited data is available on its 'real-world' impact on anticoagulation uptake and subsequent AF-related hospitalisation and stroke rates. Purpose: To evaluate the long-term impact of the introduction of a community-wide integrated AF service based in a secondary care hospital. Methods: In September 2017 we implemented a new integrated pathway for patients with newly diagnosed 'symptomatic' atrial arrhythmias across two regions (population 450, 000) in England in collaboration with primary care. All patients were seen in a one-stop multi-professional clinic (Arrhythmia nurse and Electrophysiologist with ECG and echocardiogram) within 2 weeks. They underwent standardised screening for modifiable risk factors, counselling regarding diagnosis/ anticoagulation and received an individualised AF management plan as well as access to a nurse-led telephone helpline. We followed up the first 126 consecutive patients for a period of 12 months. Results: Baseline characteristics are shown in table 1, showing a high incidence of modifiable risk factors (previously un-identified in the majority). After review in clinic, 30-day AF-related readmission rates to hospital were low (1.6%, n=2) as compared to historical local data (5.8%). This was sustained at 3 months (4.7%, n=6) and at 12 months (7.9%, n=10). 99% of 83 of eligible patients (CHA2DS2-VASc score of >2 with no major contra-indications) received oral anticoagulation. Over 12 months follow-up, rates of TIA/stroke was low (n=3, 2.4%). All-cause mortality was also low (n=1, 0.8%). NHS England region-wide data showed a marked reduction in percentage of total stroke admissions with history of AF not taking anticoagulation at stroke presentation in 2018/19 as compared to 2017/18 across our two regions; this was lower than the national average and the lowest within West Yorkshire ( figure 1 ). 2 Conclusions: An integrated service for AF management implemented community-wide was associated with high uptake of oral anticoagulation among eligible patients and low rates of AF-related hospitalisations and all-cause mortality. Across the community, among stroke admissions with AF at presentation, a lower percentage of patients without anticoagulation was observed in comparison with previous years and neighbouring regions. Conflict of Interest: none